3 Year simvastatin treatment and lens nuclear back scattering. Issue 5 (1st May 2000) - Qian, Wen; Söderberg, Per G; Chen, Enping; Magnius, Karin; Philipson, Bo
Abstract : AIM: To determine if 3 year treatment of hypercholesterolaemia with simvastatin causes an increase of lens nuclear back scattering. METHODS: 160 patients with hypercholesterolaemia in the Scandinavian Simvastatin Survival Study (4S) were followed for 3 years. Half (80) of the patients took simvastatin and half (80) received placebo. The lens was photographed with a Topcon SL-45 slit lamp camera at the beginning and at 1 year intervals. A common lens nuclear area was used for measuring lens nuclear back scattering. RESULTS: Nuclear back scattering increased with age and there was more pronounced scattering in women than in men. Lens nuclear back scattering did not differ significantly between the simvastatin and placebo groups, but the power was low (0.2). Lens nuclear back scattering increased during the study period independently of baseline back scattering, age, and sex for both groups. CONCLUSION: Although no significant difference was found between the simvastatin and placebo groups, the currently available data are insufficient for exclusion of the possibility that taking simvastatin during a 3 year period increases nuclear back scattering. However, a possible minor increase of nuclear back scattering is clinically irrelevant considering known beneficial effects of simvastatin on coronary heart disease.